Keabsahan Perkawinan Virtual Akibat Pandemi Covid-19 Menurut Undang-Undang Perkawinan dan Hukum Islam - Giani Prani Putri Prasasti; Susilowati Suparto; Eidy Sandra (Publikasi Indonesia, 2023)
The Pandemic of Covid-19 caused to virtual marriage phenomenon. Such event draws attention to many people and by such brought up question about the validity of it, because either one of the brides is not present in the same place, as such the marriage doesn’t include one of its factors called ittihad al-majlis. Doubts about the validity of virtual marriage impacts the registration for marriage that is used as an authentic proof that can help keep the rights of a marriage. This research aims to obtain legal certainty about the legitimacy of virtual marriage which held due to the Covid-19 Pandemic and to find out legal remedies against unregistered virtual marriage. This research uses a normative juridicial as its approaching method and descriptive analytical as the specification of research, which describe the problem of this research with the current regulations, in this case regarding the validity of virtual marriage, which then analyzed use Islam regulation, and secondary data in the form of primary legal materials, secondary legal materials, and tertiary legal materials. Juridicial methods was used as data analysis. This result of the research concludes, firstly, virtual marriage which held due to the Covid-19 Pandemic based on Article 2 of the UUP is legal and based on Islamic law is also legal because ulama 4 mahzab, reasoning of qiyas, the statement from the chairman of Fatwa MUI, and the statement from South Jakarta Religion Court Judge, namely by guaranteeing the certainty and correctness of the pronunciation on ijab kabul. Secondly, the virtual marriage that hasn’t been registered can appeal for isbat nikah to the Religion Court stated by Article 7 section 3 letter c of the KHI.